Selbst organisiertes Lernen am Gymnasium Eine Untersuchung interindividueller Unterschiede bei Schülerinnen und Schülern im Umgang mit der Lernerautonomie - Hilbe, Robert (Verlag Barbara Budrich, 2022)
Independent knowledge acquisition and learning organisation are key qualifications of the information society. The Mixed Methods study examines inter-individual differences among pupils in dealing with self-organised learning at secondary school level. Four types of learners are identified, which are characterised in more detail by a content-analysis of interviews and two case studies. Recommendations for the design of self-organised learning units are derived from the results.